INTERNALIZING THE CULTURAL VALUES OF ANDE-ANDE LUMUT FOLKLORE THROUGH THE SOCIODRAMA METHOD IN NARRATIVE TEXT LEARNING IN SENIOR HIGH SCHOOLS - Taufik Nugroho (Universitas Nasional, 2019)
ABSTRAK Mata pelajaran Bahasa Indonesia pada Kurikulum 2013 bertujuan agar siswa mampu mendengarkan, membaca,memirsa, berbicara, dan menulis. Kompetensi dasar dikembangkan berdasarkan tiga hal yang saling berhubungan. Ketiga hal tersebut adalah bahasa, sastra, dan literasi. Makalah ini bertujuan mengapresiasi karya sastra Indonesiaberupa teks folklor Ande-Ande Lumut dengan menggunakan metode sosiodrama. Manfaat menggunakan metodesosiodrama, diantaranya: (1) mempertinggi perhatian siswa melalui adegan-adegan; (2) membuat siswa mengertipersoalan sosial psikologis dan ikut merasakan perasaan dan pikiran orang lain; dan (3) membuat siswa dapatmenempatkan diri pada tempat orang lain dan memperdalam pengertian mereka tentang orang lain. Penulisanmakalah ini menggunakan metode kualitatif deskriptif dengan teknik kepustakaan. Hasil dari penulisan makalah inidiharapkan dapat menjadi salah satu rujukan bagi para guru atau praktisi pendidikan Bahasa Indonesia, utamanyapembelajaran teks folklor Indonesia dalam menghayati nilai-nilai budaya yang terkandung di dalamnya. Kata Kunci: Nilai Budaya, Folklor, Sosiodrama ABSTRACT In general, the 2013 Indonesian Language curriculum aims to enable students to listen, read, view, speak and write.Basic competencies are developed based on three things that are interconnected and mutually supportive indeveloping students' knowledge, understanding, and having the competence to listen, read, view, speak, and write.These three things are language, literature and literacy.The purpose of this paper is to appreciate Indonesianfolklore Ande-Ande Lumut by using the sociodrama method. Some important benefits using this method are (1)heightening students' attention through scenes, which does not always occur in the lecture or discussion method, (2)making students understand psychological social problems and participate to feel the feelings and thoughts ofothers, and (3) making students put themselves in other people's places and deepen their understanding of others.The writing of this paper uses a descriptive-qualitative method with library study. The results of writing this paperare expected to become one of the references for teachers or practitioners in the field of Indonesian languageeducation, especially learning folklore texts in living the cultural values contained in them. Key words: Cultural Values, Folklore, Sociodrama